An intermediate step to resource peripheries: The strategic coupling of gateway cities in the upstream oil and gas GPN. Issue 92 (June 2018) - Breul, Moritz; Revilla Diez, Javier
Highlights: Extraction-related activities concentrate in gateway cities. This spatial configuration inhibits economic development in resource peripheries. Varying state roles have shaped this spatial configuration. Jakarta's role stems from the regulator and producer role of the Indonesian state. The Singaporean state transformed regional assets to the industry's strategic needs. Abstract: The actual extraction of natural resources is territorially tied to their geological occurrence. However, previous studies have shown that a direct strategic coupling with commodity source regions has become increasingly uncommon in the context of the contemporary organization of extractive industries. Instead, extractive Global Production Networks (GPNs) create an 'intermediate' step and bundle their activities in so called 'gateway cities' outside the resource periphery, from where they integrate the latter. Understanding the underlying rationales and the explicit functions that make these cities essential for the larger production network is crucial in order to understand the spatial configuration of the GPN and the (limited) opportunities for resource peripheries. This paper therefore explores the strategic coupling of two distinct gateway cities (Singapore, Jakarta) in the upstream oil and gas GPN. Based on 31 interviews the article highlights how varying state roles have shaped the spatial configuration of this particular GPN. While the Singaporean state contributed to 'holding down' the GPN by transforming its regional assets to the strategic needs of the industry, the 'detour' via Jakarta is a consequence of the regulator and producer role of the Indonesian state as well as the spatially unequally distributed institutional capacities across Indonesia. Both influences inhibit opportunities for economic development in commodity source regions.